2019
DOI: 10.1038/s41467-019-08524-3
|View full text |Cite
|
Sign up to set email alerts
|

PLCβ2 negatively regulates the inflammatory response to virus infection by inhibiting phosphoinositide-mediated activation of TAK1

Abstract: Excessive or uncontrolled release of proinflammatory cytokines caused by severe viral infections often results in host tissue injury or even death. Phospholipase C (PLC)s degrade phosphatidylinositol-4, 5-bisphosphate (PI(4,5)P2) lipids and regulate multiple cellular events. Here, we report that PLCβ2 inhibits the virus-induced expression of pro-inflammatory cytokines by interacting with and inhibiting transforming growth factor-β-activated kinase 1 (TAK1) activation. Mechanistically, PI(4,5)P2 lipids directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…In addition, except that viruses inhibited positive regulators, such as β-arrestin 2, to achieve immune evasion in the present study, some other viruses also use the opposite strategy that enhances the expression of negative regulators to eventually evade the host immune response. For example, one of our previous studies demonstrated that virus-induced PLCβ2 negatively regulates virus-induced proinflammatory responses by inhibiting the activation of TAK1 48 . However, while the devil climbs a post, the priest climbs ten.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, except that viruses inhibited positive regulators, such as β-arrestin 2, to achieve immune evasion in the present study, some other viruses also use the opposite strategy that enhances the expression of negative regulators to eventually evade the host immune response. For example, one of our previous studies demonstrated that virus-induced PLCβ2 negatively regulates virus-induced proinflammatory responses by inhibiting the activation of TAK1 48 . However, while the devil climbs a post, the priest climbs ten.…”
Section: Discussionmentioning
confidence: 99%
“…PLCβ2 knockout mice are more resistant to infections by viruses. Viral infections cause uncontrolled release of proinflammatory cytokines through activation of the MAPKKK, TAK1 (TGFβ-activated kinase 1) [186]. TAK1 interacts with PLCβ2 as well as with PI(4,5)P 2 .…”
Section: Plcβ2mentioning
confidence: 99%
“…Thus, it would be interesting to test whether DAG production or [Ca 2+ ] i itself contributes to the restoration of tLTP and contextual fear memory impairment. Methodologically, although we directly injected m-3M3FBS into the dorsal and ventral hippocampi of 5XFAD mice, other studies administered m-3M3FBS via intraperitoneal injections [ 93 , 94 ]. To enhance the therapeutic effectiveness in neurological disorders, it remains to be determined whether oral administration or intraperitoneal injection of m-3M3FBS can pass the blood-brain barrier to activate PLCβ directly.…”
Section: Discussionmentioning
confidence: 99%